Polarizer

By forming low boric acid and low iodine concentration areas in the end areas of the polarizer and adopting alkali treatment process, the problems of cracks and deiodation of the polarizer in an alternating environment of low and high temperatures are solved, and more stable structural and appearance performance is achieved.

CN114286956BActive Publication Date: 2024-12-13SUMITOMO CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080059828.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-12
Filing Date
2020-08-06
Publication Date
2024-12-13
Estimated Expiration
2040-08-06

AI Technical Summary

Technical Problem

After cooling under low-temperature drying conditions, existing polarizers are exposed to high-temperature drying environments, cracks and deiodation in the end areas are easily generated, affecting their stability and appearance.

Method used

A polarizer is designed to form low boric acid and low iodine concentration areas in the end area, and a specific concentration gradient structure is formed through the alkali treatment process to inhibit the generation of cracks and deiodation. The polarizing plate is composed of a resin film containing boric acid and iodine. The length of the low boric acid concentration part is 15 μm or more and 100 μm or less, and the length of the low iodine concentration part is 19 μm or more and 100 μm or less, and is formed along the outer edge of the polarizing plate.

Benefits of technology

During repeated thermal shock tests for condensation, cracks are effectively suppressed, and the deiodated part is not easily conspicuous, improving the stability and appearance performance of the polarizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114286956B_ABST
    Figure CN114286956B_ABST
Patent Text Reader

Abstract

The present invention provides a polarizing plate, which can suppress the generation of cracks in a condensation heat shock test under repeated low-temperature (-40°C) condensation conditions and high-temperature (85°C) conditions, and makes the deiodination site in the end region inconspicuous. The polarizing plate of the present invention is a resin film containing boric acid and iodine, and a low boric acid concentration site is formed in the region including the end when viewed from above, and the concentration of boric acid is lower than the concentration of boric acid in the inner region at an inner distance of more than 500 μm relative to the end, and a low iodine concentration site is formed in the region including the end, and the concentration of iodine is lower than the concentration of iodine in the inner region, and the length of the low iodine concentration site from the end is more than 19 μm and less than 100 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polarizing plate, a polarizing plate including the polarizing plate, a method for producing the polarizing plate, and an image display device. Background Art

[0002] Patent Document 1 proposes a polarizing plate in which a portion having a lower boric acid content concentration than other portions is formed at an end portion.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-206641 Summary of the invention

[0006] Problems to be solved by the invention

[0007] The polarizing plate described in Patent Document 1 has a portion with a low boric acid concentration at the end, and also has a deiodinated portion with a width of more than 300 μm from the end when viewed from above. Figure 4 (b)).

[0008] The object of the present invention is to provide a polarizer, which is exposed to low temperature (-40°C) drying conditions for cooling, exposed to external air at 25°C to be set to a condensation state, and then exposed to high temperature (85°C) drying. In a condensation heat shock test in which such operations are repeatedly performed, the generation of cracks is suppressed and the site of deiodination in the end area is not noticeable. A polarizing plate having the polarizer and their manufacturing methods are provided.

[0009] Means for solving problems

[0010] The present invention provides the following polarizing film, polarizing plate, image display device and manufacturing method.

[0011] [1] A polarizing plate comprising a resin film containing boric acid and iodine,

[0012] A low boric acid concentration portion is formed in a region including the end portion when viewed from above, wherein the concentration of boric acid in the low boric acid concentration portion is lower than the concentration of boric acid in an inner region at an inner distance of 500 μm or more relative to the end portion,

[0013] In the region including the end, a low iodine concentration region is formed, the iodine concentration of which is lower than the iodine concentration in the inner region,

[0014] The length of the low iodine concentration portion from the end portion is 19 μm or more and 100 μm or less.

[0015] [2] The polarizing plate according to [1], wherein the concentration of boric acid in the low boric acid concentration portion decreases as it approaches the end portion from the inner side when the polarizing plate is viewed from above.

[0016] [3] The polarizing plate according to [1] or [2], wherein the length of the low boric acid concentration portion from the end is 15 μm or more.

[0017] [4] The polarizing plate according to any one of [1] to [3], wherein the low boric acid concentration region and the low iodine concentration region are formed along an outer edge of the polarizing plate.

[0018] [5] A polarizing plate according to any one of [1] to [4], wherein the polarizing plate has a non-uniform portion when viewed from above, and the low boric acid concentration portion and the low iodine concentration portion are formed in an end region included in the non-uniform portion.

[0019] [6] The polarizing plate according to [5], wherein the irregularly shaped portion is a concave portion provided at the peripheral portion, or a through hole provided in the polarizing plate surface.

[0020] [7] A polarizing plate comprising the polarizing plate according to any one of [1] to [6], and an optical film disposed on one side or both sides of the polarizing plate.

[0021] [8] An image display device comprising the polarizing plate described in [7].

[0022] [9] The image display device according to [8], which has a camera hole.

[0023]

[10] A method for producing a polarizing plate, the polarizing plate comprising a polarizer which is a resin film containing boric acid and iodine, and an optical film disposed on one side or both sides of the polarizer,

[0024] The manufacturing method includes an alkali treatment step of bringing an alkaline solution at a temperature of 50° C. or less into contact with an end portion of the resin film containing boric acid and iodine for a period of time within 6 minutes.

[0025]

[11] The method for producing a polarizing plate according to

[10] , wherein the alkaline solution contains water.

[0026]

[12] The method for producing a polarizing plate according to

[10] or

[11] , wherein the alkaline solution is a solution in which a strong alkaline compound is dissolved in a solvent.

[0027]

[13] The method for producing a polarizing plate according to

[12] , wherein the strong alkaline compound comprises sodium hydroxide and / or potassium hydroxide.

[0028]

[14] A method for manufacturing a polarizing plate according to any one of

[10] to

[13] , further comprising a forming step, wherein the resin film containing boric acid and iodine is formed into a predetermined shape by cutting and / or punching, and the resin film after the forming step is subjected to the alkali treatment step.

[0029] Effects of the Invention

[0030] According to the present invention, a polarizer can be provided, which is exposed to low-temperature (-40°C) drying conditions for cooling, then exposed to external air at 25°C to be in a condensation state, and then exposed to high-temperature (85°C) drying. In a condensation heat shock test (hereinafter referred to as a condensation heat shock test for simplicity) in which such operations are repeated, the generation of cracks is suppressed, and the site of deiodination in the end area is not noticeable. A polarizing plate having the polarizer and their manufacturing methods can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic cross-sectional view showing a polarizing plate according to one embodiment of the present invention.

[0032] Figure 2 This is a schematic plan view of a polarizing plate for explaining a low boric acid concentration portion.

[0033] Figure 3 This is a schematic plan view of a polarizing plate for explaining a low iodine concentration area.

[0034] Figure 4 This is a schematic cross-sectional view showing an example of an image display device having a camera hole.

[0035] Figure 5 This is a schematic plan view showing a polarizing plate according to one embodiment of the present invention.

[0036] Figure 6 It is a schematic plan view showing a polarizing plate according to one embodiment of the present invention.

[0037] Figure 7 It is a schematic plan view showing a polarizing plate according to one embodiment of the present invention.

[0038] Figure 8 It is a schematic plan view showing a polarizing plate according to one embodiment of the present invention.

[0039] Fig. 9 This is a schematic cross-sectional view showing a polarizing plate according to one embodiment of the present invention.

[0040] Fig.10 It is a schematic diagram showing an example of the first stacked body.

[0041] Fig.11It is a schematic diagram showing an example of the second stacked body and the end mill.

[0042] Fig.12 This is a schematic diagram showing an example of a cutting process.

[0043] Fig.13 It is a schematic diagram for explaining the measurement sample of the Example.

[0044] Fig.14 It is a schematic cross-sectional view showing a first stacked body according to the embodiment.

[0045] Fig.15 It is a schematic plan view showing a polarizing plate according to an example.

[0046] Fig.16 The TOF-SIMS analysis results and end observation results of Example 1 are shown.

[0047] Fig.17 The TOF-SIMS analysis results and end observation results of Comparative Example 1 are shown.

[0048] Fig.18 The TOF-SIMS analysis results and end observation results of Comparative Example 2 are shown. DETAILED DESCRIPTION

[0049] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings, but the present invention is not limited to the following embodiments. In all the following drawings, in order to facilitate the understanding of each component, the proportions of the components shown in the drawings are appropriately adjusted, and the proportions of the components shown in the drawings are not necessarily consistent with the proportions of the actual components. In the accompanying drawings, the same symbols are added to the same components. The X, Y and Z shown in each figure represent three mutually orthogonal coordinate axes. The directions shown by the XYZ coordinate axes in each figure are common in each figure.

[0050] <Polarizing Plate>

[0051] The polarizer is a resin film containing boric acid and iodine. The resin film containing boric acid and iodine can be, for example, a resin film in which iodine is adsorbed and oriented on a uniaxially stretched polyvinyl alcohol resin film, and the polyvinyl alcohol molecular chains are cross-linked by boric acid. The polarizer can be an absorption-type polarizer having the following properties, that is, absorbing linear polarized light having a vibration plane parallel to the absorption axis and transmitting linear polarized light having a vibration plane orthogonal to the absorption axis (parallel to the transmission axis). The polarizer can be used as a polarizing plate after bonding an optical film on one or both sides with an adhesive or a bonding agent.

[0052] like Figure 1As shown, the polarizing plate 1 can be formed by arranging the polarizing plate 2 between the first optical film 3 and the second optical film 4. Hereinafter, the first optical film and the second optical film may be collectively referred to as an optical film.

[0053] The polarizing plate has a low boric acid concentration portion in the region including the end portion when viewed from above, and the boric acid concentration is lower than the boric acid concentration in the inner region (hereinafter also referred to as the inner region) at a distance of 500 μm or more from the end portion. In the inner region, the boric acid concentration and the iodine concentration can be made substantially the same. Figure 2 As shown, the polarizer 2 can have a low boric acid concentration portion 30 in a region including the end portion when viewed from above, and an inner region 32 at a distance of more than 500 μm inside relative to the end portion. The inner region 32 can include an area for displaying an image when incorporated into a liquid crystal display device. The boric acid concentration in the intermediate region 31 between the low boric acid concentration portion 30 and the inner region 32 is generally substantially the same as that of the inner region 32. In this specification, the term "viewed from above" refers to observation in the thickness direction of the polarizer. The concentration of boric acid is the concentration of boric acid per unit area including the thickness direction of the polarizer, and is measured, for example, using time-of-flight secondary ion mass spectrometry (TOF-SIMS) described in the Example column below. In this specification, boric acid contains, for example, boric acid molecules (H3BO3) and boric acid ions (BO3 3- ).

[0054] Since the polarizing plate has a low boric acid concentration portion, the generation of cracks tends to be suppressed in the condensation heat shock test. The condensation heat shock test can be performed according to the method described in the Examples section described later.

[0055] The concentration of boric acid in the low boric acid concentration portion is preferably lower as it approaches the end portion in the direction from the inside toward the end portion when the polarizer is viewed from above, from the viewpoint of suppressing cracks and making discoloration less noticeable in the appearance of the polarizer. The end portion of the polarizer preferably does not contain boric acid.

[0056] The length of the low boric acid concentration portion from the end can be, for example, greater than 15 μm. From the viewpoint of crack suppression, it is preferably greater than 15 μm and less than 200 μm, more preferably greater than 15 μm and less than 150 μm, further preferably greater than 15 μm and less than 100 μm, and particularly preferably greater than 15 μm and less than 50 μm.

[0057] The boundary between the region formed with the low boric acid concentration part and the region outside it can be obtained according to the boric acid concentration distribution, which is obtained in the time-of-flight secondary ion mass spectrometry (TOF-SIMS) described in the embodiment column described later, and is the boric acid concentration distribution relative to the distance from the end. For example, in the case of a region where the boric acid ion strength is constant and can be read in the boric acid concentration distribution, the average value of the boric acid ion strength in the region can be obtained, and the position from the end to the boric acid ion strength is the above average value is set as the low boric acid concentration part. In the case of a region where it is difficult to read the above-mentioned boric acid ion strength constant in the boric acid concentration distribution, in the boric acid concentration distribution, the average value of the boric acid ion strength in the range of 30 μm inside the point with the maximum boric acid ion strength is obtained, and the position from the end to the boric acid ion strength is the above average value is set as the low boric acid concentration part.

[0058] The polarizing plate has a low iodine concentration portion in a region including the end portion, wherein the iodine concentration is lower than the iodine concentration in a region at an inner distance of 500 μm or more from the end portion. The length of the low iodine concentration portion from the end portion is 19 μm or more and 100 μm or less. Figure 3 As shown, the polarizer 2 has a low iodine concentration area 33 in the region including the end portion when viewed from above. The iodine concentration of the intermediate region 34 between the low iodine concentration area 33 and the inner region 32 is generally substantially the same as that of the inner region 32. The low iodine concentration area is formed in the region through which light is transmitted when the polarizer is viewed from above using an optical microscope. Iodine includes, for example, iodine molecules (I2), polyiodine complexes (I3 - 、I5 - ), iodide ion (I - ).

[0059] When the length from the end of the low iodine concentration portion is less than 100 μm, there is a tendency to make the low iodine concentration portion less noticeable in the appearance of the polarizer. In addition, when the length from the end of the low iodine concentration portion is more than 19 μm, there is a tendency to easily suppress cracks. From the viewpoint of making deiodination less noticeable, the length from the end of the low iodine concentration portion is preferably more than 19 μm and less than 50 μm.

[0060] According to the method described in the embodiment 1 column described later, low iodine concentration position and high iodine concentration position are distinguished.In the optical microscope image that is imported on the personal computer and has implemented image processing, the low iodine concentration position is usually the area where the brightness reaches more than 180, the brightness of the inner area is more than 100 and below 140, and the brightness of the iodine concentration in the middle area between the low iodine concentration position and the inner area is usually less than 180.

[0061] The low boric acid concentration portion and the low iodine concentration portion may be portions that partially overlap each other, or one portion may completely overlap the other portion. From the viewpoint of suppressing cracks and making deiodination less noticeable, it is preferred that the low iodine concentration portion completely includes the low boric acid concentration portion.

[0062] A plurality of low boric acid concentration sites and a plurality of low iodine concentration sites may be formed in a plurality of regions of the polarizing plate.

[0063] From the viewpoint of crack suppression, it is preferred to form a low boric acid concentration portion and a low iodine concentration portion along the outer edge of the polarizer. The low boric acid concentration portion and the low iodine concentration portion may be formed along the entire outer edge of the polarizer or along a portion of the outer edge of the polarizer.

[0064] The polarizer may have a shaped portion. When viewed from above, the shaped portion may be a concave portion formed at the outer edge and a through hole formed in the polarizer surface. In addition, the direction of the tangent of the shaped portion may be discontinuous, for example, it may be a shape where two straight lines intersect, and the radius of curvature at the intersection may be 0 mm. In the case where the direction of the tangent is discontinuous and the radius of curvature at the intersection is small (usually less than 3 mm, preferably less than 2 mm, and more preferably less than 1 mm), the anti-crack effect of the present invention is significant. The polarizer may have two or more shaped portions at the outer edge and / or in the surface. The specific examples of the shape of the shaped portion and the position formed can be applied to the examples of the shape of the shaped portion and the position formed in the description of the polarizing plate described later.

[0065] When the polarizer has a non-shaped portion, from the viewpoint of suppressing cracks and making the low iodine concentration portion less noticeable, it is preferred that a low boric acid concentration portion and a low iodine concentration portion are formed in an edge region included in the non-shaped portion.

[0066] In a condensation heat shock test, a polarizer having an irregular portion is prone to stress concentration at the irregular portion, which tends to cause cracks. By forming a low boric acid concentration area in the end region included in the irregular portion, it is easy to suppress the generation of cracks in the condensation heat shock test.

[0067] In addition, if Figure 4 As shown, when a polarizing plate 21 having a polarizing sheet with a special-shaped portion is used in an image display device 20 having a camera hole 22, a cover glass 24, an adhesive layer 25, a liquid crystal panel 23, a polarizing plate 26, a camera 27, and a light-shielding tape 28, Figure 4In the figure, the part surrounded by the circle can be directly observed, so the low iodine concentration part formed in the large area at the end included in the irregular part of the polarizer 21 is easy to become conspicuous, and as a result, there is a tendency to reduce the design. However, even when the polarizer of the present invention is used for the image display device with a camera hole as described above, it is not easy to make the low iodine concentration part conspicuous, and there is a tendency to be excellent in design.

[0068] When the irregularly shaped portion is a concave portion, from the viewpoint of crack suppression, the depth direction of the concave portion is preferably orthogonal to the absorption axis (stretching direction), or may intersect at an angle of 30 degrees or more and usually 60 degrees or less.

[0069] The polarizer can be in the form of a long strip or a paper. When the polarizer is in the form of a paper, the overall shape of the polarizer can be a square or a rounded square when viewed from above. The so-called rounded square refers to a shape in which one or more of the corners of the square are curved, that is, one or more of the corners of the square are rounded, and the so-called square refers to a shape in which none of the four corners are rounded. In addition, in this specification, the so-called square refers to a rectangle or a square. When the polarizer is a rounded square, one or more of the four corners of the polarizer can be rounded. The overall shape of the polarizer when viewed from above can be a polygon, a circle, or an ellipse. The specific example of the overall shape of the polarizer when viewed from above can be applied to the illustration of the overall shape of the polarizer in the description of the polarizer described later.

[0070] The thickness of the polarizer can be, for example, 1 μm or more and 50 μm or less, or 3 μm or more and 15 μm or less. The thinner the polarizer, the easier it is to suppress the shrinkage or expansion of the polarizer itself due to temperature changes, and there is a tendency to easily suppress the change in the size of the polarizer itself. As a result, it is difficult to apply stress to the polarizer, and there is a tendency to easily suppress cracks in the polarizer.

[0071] Figure 5 Represents the overall shape of the polarizer 2 when viewed from above. The overall shape of the polarizer 2 is a rounded square, and has a concave portion as a special-shaped portion. The concave portion is made parallel to the absorption axis (stretching direction) in the depth direction. In the polarizer 2, region I (11) and region II (12) are locally formed along a part of the periphery including the concave portion, and are formed at the outer edge portion including the concave portion. Region I (11) is a region where a low boric acid concentration portion and a low iodine concentration portion are formed at the same time. Region II (12) can be a region where either a low boric acid concentration portion or a low iodine concentration portion is formed.

[0072] <Polarizing plate>

[0073] A polarizing plate according to another embodiment of the present invention is a polarizing plate comprising the above-mentioned polarizing plate and an optical film provided on one or both sides thereof. The optical film may be bonded to the polarizing plate via an adhesive layer comprising an adhesive or a pressure-sensitive adhesive.

[0074] like Figure 1 As shown, the polarizing plate 1 of this embodiment includes at least one pair of optical films (3, 4) and a film-shaped polarizing plate 2 located between the pair of optical films (3, 4). In the following, for the convenience of description, the polarizing plate 1 formed by the polarizing plate 2 and the pair of optical films (3, 4) is mainly described. However, as described later, the number of optical films included in the polarizing plate is not limited to two.

[0075] The optical film refers to a film-like member forming the polarizing plate 1 (excluding the polarizer 2 itself). For example, the optical film includes a protective film and a release film. Each optical film may not have a specific optical function when used alone. The "film" (optical film) may be referred to as a "layer" (optical layer). A pair of optical films (3, 4) each includes a resin. However, the composition of each optical film (3, 4) is not limited.

[0076] The polarizing plate 2 and the optical films (3, 4) are overlapped directly or indirectly. For example, another optical film may be present between the polarizing plate 2 and the optical films (3, 4). The polarizing plate 2 may be overlapped with the optical films (3, 4) via an adhesive layer.

[0077] Figure 6 It is a plan view showing the surface of the polarizing plate 1 according to the present embodiment. Figure 6 The cross section of the polarizing plate 1 shown is perpendicular to the surface of the polarizing plate 1. In addition, the cross section of the polarizing plate 1 is perpendicular to the outer periphery 1p of the polarizing plate 1 located inside the recessed portion 13 formed in the polarizing plate 1.

[0078] like Figure 6 As shown, the recess 13 is formed in the periphery 1p of the polarizing plate 1. That is, the recess 13 exists in the periphery 1p of the polarizing plate 1. The recess 13 may be referred to as a depression, a notch or a notch. The recess 13 may penetrate the polarizing plate 1 in a direction (Z-axis direction) perpendicular to the surface (light-receiving surface) of the polarizing plate 1. The so-called periphery 1p of the polarizing plate 1 may be referred to as the outer edge or outline of the polarizing plate 1 (light-receiving surface) observed from a direction perpendicular to the light-receiving surface of the polarizing plate 1 (top view direction).

[0079] The inner corner 13c of the recess 13 may be a right angle or a curve when viewed from above. That is, the end face of the polarizing plate 1 located at the inner corner 13c of the recess 13 may be a curved surface. That is, the inner corner 13c of the recess may be chamfered. By making the inner corner 13c of the recess 13 a curve when viewed from above, it is easier to suppress cracks at the inner corner 13c of the recess 13 than when it is a right angle. Figure 4 As shown, the corners at both ends of the recess 13 and the corners at the four corners of the polarizing plate 1 may be chamfered.

[0080] The width of the recess 13 (the width of the recess 13 in the X-axis direction) is not particularly limited, and for example, it can be greater than 3 mm and less than 160 mm. The depth of the recess 13 (the width of the recess 13 in the Y-axis direction) is not particularly limited, and for example, it can be greater than 0.5 mm and less than 160 mm. The length of the side (short side) of the polarizing plate 1 formed with the recess 13 is not particularly limited, and for example, it can be greater than 30 mm and less than 90 mm. The length of the side (long side) of the polarizing plate 1 without the recess 13 is not particularly limited, and for example, it can be greater than 30 mm and less than 170 mm.

[0081] The thickness of the entire polarizing plate 1 is not particularly limited, and may be, for example, 30 μm or more and 300 μm or less.

[0082] Figure 6 The recess 13 shown is a quadrilateral (rectangle) with rounded corners. However, the shape of the recess 13 is not limited. For example, the recess 13 may be a square. The recess 13 may also be a polygon other than a quadrilateral or a triangle. Figure 7 As shown in (a) to (h) in FIG. 1 , the shape of the recess 13 may be a rounded rectangle, a rectangle, a semicircle, a V-shape, a shape combining a straight line and a curve, or a curved shape. Figure 7 The shapes of the polarizing plate 1 shown in (a) to (h) are all symmetrical, but the shape of the polarizing plate 1 may be asymmetrical. A plurality of recesses 13 may be formed on the periphery 1p of the polarizing plate 1. The plurality of recesses 13 may be formed on one side forming the periphery 1p of the polarizing plate 1. The recesses 13 may be formed by cutting off at least one of the four corners of the quadrilateral polarizing plate 1.

[0083] The overall shape of the polarizing plate 1 excluding the recess 13 is approximately a quadrilateral (rectangle). However, the shape of the polarizing plate 1 is not limited. For example, the shape of the polarizing plate 1 may be a square. The shape of the polarizing plate 1 may also be a polygon other than a quadrilateral, a circle, or an ellipse. The overall shape of each of the polarizing plate 2 and the optical film (3, 4) may be approximately the same as the shape of the polarizing plate 1. Figure 4 In the case of the rectangular polarizing plate 1 shown, the recessed portion 13 is formed on the short side of the polarizing plate 1 , but the recessed portion 13 may be formed on the long side of the polarizing plate 1 .

[0084] like Figure 8 As shown, the polarizing plate 1 may have a through hole in the plane when viewed from above. The diameter of the through hole may be, for example, 0.5 mm to 30 mm, preferably 1 mm to 10 mm.

[0085] (Other Embodiments of Polarizing Plate)

[0086] For example, the polarizing plate may include another optical film including a resin in addition to a pair of optical films including a first optical film and a second optical film. That is, the polarizing plate may include more than three optical films. Fig. 9 As shown, the polarizing plate may include a first optical film 3 and a second optical film 4, a polarizing plate 2 located between the first optical film 3 and the second optical film 4, and a third optical film 15 overlapping the first optical film 3. The third optical film 15 may overlap the first optical film 3 via the above-mentioned adhesive layer. The resin contained in the third optical film 15 may be at least any one of the above-mentioned resins listed as the resin contained in each of the first optical film 3 and the second optical film 4. The composition of the third optical film 15 may be the same as the composition of the first optical film 3. The composition of the third optical film 15 may also be different from the composition of the first optical film 3. The composition of the third optical film 15 may be the same as the composition of the second optical film 4. The composition of the third optical film 15 may also be different from the composition of the second optical film 4. The thickness of the third optical film 15 may be, for example, 5 μm or more and 200 μm or less. The third optical film 15 may be peeled off and removed from the polarizing plate in the manufacturing process of the image display device. That is, the third optical film 15 may be a temporary optical film.

[0087] The polarizing plate may further include an adhesive layer overlapping one of the pair of optical films, and a release film overlapping the adhesive layer. Fig. 9 The polarizing plate shown may further include an adhesive layer overlapping with the second optical film 4, and a release film overlapping with the adhesive layer. The adhesive layer may include, for example, a pressure-sensitive adhesive such as an acrylic pressure-sensitive adhesive, a rubber pressure-sensitive adhesive, a silicone pressure-sensitive adhesive, or a urethane pressure-sensitive adhesive. The thickness of the adhesive layer may be, for example, greater than 2 μm and less than 100 μm. The resin contained in the release film may be at least any one of the above-mentioned resins listed as the resin contained in each of the first optical film 3 and the second optical film 4. The composition of the release film may be the same as that of the first optical film 3. The composition of the release film may also be different from that of the first optical film 3. The composition of the release film may be the same as that of the second optical film 4. The composition of the release film may also be different from that of the second optical film 4. The thickness of the release film may be, for example, greater than 10 μm and less than 100 μm. The release film may be peeled off and removed from the polarizing plate during the manufacturing process of the image display device. The release film may be disposed on both surfaces of the polarizing plate via an adhesive layer.

[0088] The polarizing plate can be used as an optical film or layer and also has at least one selected from a reflective polarizing film, a film with an anti-glare function, a film with a surface anti-reflection function, a reflective film, a semi-transmitting reflective film, a viewing angle compensation film, a window film, an antistatic layer, a hard coating layer, an optical compensation layer, a touch sensor layer and an anti-fouling layer.

[0089] The polarizing plate may have a deformed portion in a plan view. In addition, the polarizing plate may be a square or a rounded square in a plan view.

[0090] (Optical Film)

[0091] The optical film may be a light-transmitting thermoplastic resin. The optical film may be an optically transparent thermoplastic resin. The resin forming the optical film may be, for example, a chain polyolefin resin, a cyclic olefin polymer resin (COP resin), a cellulose ester resin, a polyester resin, a polycarbonate resin, a (meth) acrylic resin, a polystyrene resin, or a mixture or copolymer thereof.

[0092] In the case where the polarizing plate has the first optical film and the second optical film, the composition of the first optical film may be completely the same as the composition of the second optical film. For example, the first optical film and the second optical film may both contain a cyclic olefin polymer resin (COP resin). Even in the case where the first optical film and the second optical film contain a cyclic olefin polymer resin (COP resin), it is easy to suppress cracks in the present invention and it is easy to make discoloration inconspicuous. In the case where the polarizing plate has the first optical film and the second optical film, the composition of the first optical film may be different from the composition of the second optical film.

[0093] The glass transition temperature of the first optical film and the second optical film is preferably 100° C. to 200° C., or 120° C. to 150° C. When the glass transition temperature of each of the first optical film and the second optical film is within the above range, the first optical film and the second optical film are easily fused to each other due to the heat generated by grinding the end portions of each optical film.

[0094] The chain polyolefin-based resin may be, for example, a homopolymer of a chain olefin such as polyethylene resin or polypropylene resin, or a copolymer containing two or more chain olefins.

[0095] Cyclic olefin polymer resins (cyclic polyolefin resins) may be, for example, ring-opening (co)polymers of cyclic olefins, or addition polymers of cyclic olefins. Cyclic olefin polymer resins may be, for example, copolymers (e.g., random copolymers) of cyclic olefins and chain olefins. The chain olefins forming the copolymers may be, for example, ethylene or propylene. Cyclic olefin polymer resins may be graft polymers obtained by modifying the above-mentioned polymers with unsaturated carboxylic acids or their derivatives, or their hydrogenates. Cyclic olefin polymer resins may be, for example, norbornene resins using norbornene monomers such as norbornene or polycyclic norbornene monomers.

[0096] The cellulose ester resin may be, for example, cellulose triacetate (triacetylcellulose (TAC)), cellulose diacetate, cellulose tripropionate or cellulose dipropionate. Copolymers thereof may also be used. Cellulose ester resins in which a part of the hydroxyl groups is modified with other substituents may also be used.

[0097] Polyester resins other than cellulose ester resins may also be used. The polyester resin may be, for example, a polycondensate of a polycarboxylic acid or a derivative thereof and a polyol. The polycarboxylic acid or a derivative thereof may be a dicarboxylic acid or a derivative thereof. The polycarboxylic acid or a derivative thereof may be, for example, terephthalic acid, isophthalic acid, dimethyl terephthalate, or dimethyl naphthalate. The polyol may be, for example, a diol. The polyol may be, for example, ethylene glycol, propylene glycol, butanediol, neopentyl glycol, or cyclohexanedimethanol.

[0098] The polyester resin may be, for example, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polytrimethylene terephthalate, polytrimethylene naphthalate, polycyclohexanedimethylene terephthalate, or polycyclohexanedimethylene naphthalate.

[0099] The polycarbonate resin is a polymer obtained by bonding polymer units (monomers) via carbonate groups. The polycarbonate resin may be a modified polycarbonate having a modified polymer skeleton or a copolymer polycarbonate.

[0100] The (meth)acrylic resin may be, for example, poly(meth)acrylate (e.g., polymethyl methacrylate (PMMA)); methyl methacrylate-(meth)acrylic acid copolymer; methyl methacrylate-(meth)acrylic acid ester copolymer; methyl methacrylate-acrylate-(meth)acrylic acid copolymer; methyl (meth)acrylate-styrene copolymer (e.g., MS resin); copolymers of methyl methacrylate and a compound having an alicyclic hydrocarbon group (e.g., methyl methacrylate-cyclohexyl methacrylate copolymer, methyl methacrylate-norbornyl (meth)acrylate copolymer, etc.).

[0101] The first optical film or the second optical film may each contain at least one additive selected from the group consisting of a lubricant, a plasticizer, a dispersant, a heat stabilizer, an ultraviolet absorber, an infrared absorber, an antistatic agent, and an antioxidant.

[0102] The thickness of the first optical film may be, for example, 5 μm to 90 μm, or 10 μm to 60 μm. The thickness of the second optical film may also be, for example, 5 μm to 90 μm, or 10 μm to 60 μm.

[0103] At least one of the first optical film and the second optical film may be a film having an optical function. The film having an optical function may be, for example, a phase difference film or a brightness enhancement film. For example, a phase difference film having an arbitrary phase difference value may be obtained by stretching the film containing the thermoplastic resin or forming a liquid crystal layer on the film.

[0104] The first optical film may be overlapped with the polarizer via an adhesive layer. The second optical film may be overlapped with the polarizer via an adhesive layer. The adhesive layer may contain a water-based adhesive such as polyvinyl alcohol. The adhesive layer may contain an active energy ray-curable resin described below.

[0105] The active energy ray-curable resin is a resin that is cured by being irradiated with active energy rays. The active energy rays may be, for example, ultraviolet rays, visible light, electron beams, or X-rays. For example, the active energy ray-curable resin may be an ultraviolet-curable resin.

[0106] The active energy ray-curable resin may be a single resin or may contain multiple resins. For example, the active energy ray-curable resin may contain a cationically polymerizable curable compound or a radically polymerizable curable compound. The active energy ray-curable resin may contain a cationically polymerizable initiator or a radically polymerizable initiator for initiating a curing reaction of the curable compound.

[0107] The cationically polymerizable curable compound may be, for example, an epoxy compound (a compound having at least one epoxy group in the molecule) or an oxetane compound (a compound having at least one oxetane ring in the molecule). The radically polymerizable curable compound may be, for example, a (meth)acrylic compound (a compound having at least one (meth)acryloyloxy group in the molecule). The radically polymerizable curable compound may also be a vinyl compound having a radically polymerizable double bond.

[0108] The active energy ray-curable resin may contain a cationic polymerization accelerator, an ion trapping agent, an antioxidant, a chain transfer agent, a tackifier, a thermoplastic resin, a filler, a flow regulator, a plasticizer, a defoamer, an antistatic agent, a leveling agent, or a solvent, etc., as necessary.

[0109] In order to improve the adhesion between the polarizer and the optical film, the bonding surface of the polarizer and / or the optical film may be subjected to surface treatment such as corona treatment, flame treatment, plasma treatment, ultraviolet irradiation treatment, primer coating treatment, saponification treatment, etc. before bonding the polarizer and the optical film.

[0110] (Other layers)

[0111] The polarizing plate may also include a front panel, a phase difference film (e.g., a layer imparting a phase difference of λ / 2, a layer imparting a phase difference of λ / 4, a positive C layer, and a layer obtained by laminating a combination of at least two layers selected from them, etc.), a protective film, a touch sensor panel, an adhesive layer, etc. The polarizing plate may also be used as a circular polarizing plate by laminating a layer imparting a phase difference of λ / 4. The polarizing plate may also be a polarizing plate with an adhesive layer.

[0112] <Method for producing polarizing plate>

[0113] The method for manufacturing a polarizing plate is a method for manufacturing a polarizing plate having a polarizing plate as a resin film containing boric acid and iodine, and an optical film disposed on one side or both sides of the polarizing plate, and is a method for manufacturing a polarizing plate including an alkali treatment step of contacting an alkaline solution at a temperature of 50° C. or less with the end of the resin film containing boric acid and iodine for a period of time of less than 6 minutes. The method for manufacturing a polarizing plate also includes, before the alkali treatment step, a polarizing plate manufacturing step (a manufacturing step of a resin film containing boric acid and iodine), a laminating step, a forming step, and a cutting step described later.

[0114] (Polarizing Plate Manufacturing Process)

[0115] The resin film containing boric acid and iodine (hereinafter also referred to as non-alkali treated polarizer) can be produced by, for example, stretching, dyeing and crosslinking a polyvinyl alcohol resin film (PVA film). The stretching, dyeing and crosslinking can be performed by known methods.

[0116] For example, first, the PVA film is stretched in a uniaxial direction or a biaxial direction. The polarizer stretched in a uniaxial direction has a tendency to have a high dichroic ratio. After stretching, the PVA film is dyed with iodine, dichroic pigment (polyiodine) or organic dye using a dyeing solution. The dyeing solution may contain boric acid, zinc sulfate, or zinc chloride. The PVA film may be washed with water before dyeing. By washing with water, dirt and anti-blocking agents are removed from the surface of the PVA film. In addition, the PVA film swells due to washing with water, and as a result, it is easy to suppress uneven dyeing (uneven dyeing). In order to crosslink the dyed PVA film, it is treated with a solution of a crosslinking agent containing boric acid (e.g., an aqueous solution of boric acid). After the treatment with the crosslinking agent, the PVA film is washed with water and then dried. After the above steps, a resin film containing boric acid and iodine is obtained.

[0117] Polyvinyl alcohol (PVA) resins are obtained by saponifying polyvinyl acetate resins. Polyvinyl acetate resins can be, for example, polyvinyl acetate as a homopolymer of vinyl acetate, or copolymers of vinyl acetate and other monomers (e.g., ethylene-vinyl acetate copolymers). Other monomers copolymerized with vinyl acetate can be ethylene, and can also be unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, or acrylamides with ammonium groups. Polyvinyl alcohol resins can also be modified by aldehydes. Modified polyvinyl alcohol resins can be, for example, partially formalized polyvinyl alcohol, polyvinyl acetal, or polyvinyl butyral. Polyvinyl alcohol resins can be polyolefin-based oriented films such as dehydrated products of polyvinyl alcohol or dehydrochlorinated products of polyvinyl chloride. Dyeing can be performed before stretching, or stretching can be performed in a dyeing solution. The length of the stretched resin film can be, for example, 3 to 7 times the length before stretching. The polyvinyl alcohol resin film can be in the form of a long strip or in the form of paper.

[0118] (Lamination process)

[0119] In the lamination step, the first laminate is prepared by laminating the non-alkali treated polarizer and the optical film in an overlapping manner. The non-alkali treated polarizer and the optical film may be in the form of long strips. In the case where the non-alkali treated polarizer is overlapped and disposed between a pair of optical films, Fig.10 As shown, in the first laminate 10, the non-alkali treated polarizing plate 7 is located between a pair of optical films (5, 9).

[0120] The optical film can be bonded to the polarizing plate via an adhesive layer.

[0121] In the lamination process, an adhesive layer may be formed on the outermost surface of either side of the first laminate 10. For example, an adhesive layer may be formed by applying an adhesive to the surface of either side of the pair of optical films (5, 9) on the side opposite to the non-alkali treated polarizer 7, and a separator film that can be peeled off from the adhesive layer is attached thereto, thereby forming an adhesive layer. In addition, in the lamination process, a protective film that can be peeled off from the optical film may be attached to the outermost surface of either side of the first laminate 10.

[0122] (Forming process)

[0123] In the forming process, the size of the first stack 10 can be adjusted to a size that is easy to process. In addition, a special-shaped portion can be formed on the outer edge of the first stack 10 by punching or cutting. The cutting and / or punching process can be performed by using a cutting knife, a punching knife, or irradiating a laser. The laser can be a CO2 laser. In the forming process, the long strip of the first stack can be made into a paper-like first stack.

[0124] In the forming step, the first stacked body may be cut or punched individually or in a state where a plurality of sheets are stacked.

[0125] (Cutting process)

[0126] The method for manufacturing a polarizing plate may further include a cutting step of bringing an end mill into contact with the outer periphery of the first stack or the second stack described later, and moving the end mill along the outer periphery of the stack. Fig.10 As shown, the positions of the ends of the non-alkali treated polarizing plate 7 and the optical films (5, 9) can be aligned over the entire periphery of the first laminate 10 before the cutting step.

[0127] like Fig.11 and Fig.12 As shown in FIG. 1 , the end mill 50 used in the cutting process has a protruding blade (edge) 50e on the side surface substantially parallel to the rotation axis 50a thereof. In the cutting process, the side surface of the end mill 50 is brought into contact with the outer periphery (end surface) of the first stack 10, and the rotating end mill 50 is moved along the outer periphery of the first stack 10. For example, the rotating end mill 50 may be moved along the outer periphery of the first stack 10. Fig.12 As a result, the outer periphery (end face) of the first stack 10 is cut or ground by the blade 50e, and the outer periphery (end face) of the first stack 10 becomes smooth, forming a concave portion 13, and the inner corner of the concave portion 13 is chamfered. Fig.11 As shown, after a plurality of first stacks 10 are stacked to form a second stack 100, the side surface of the end mill 50 is brought into contact with the outer periphery (end surface) of the second stack 100, and the rotating end mill 50 is moved along the outer periphery of the second stack 100. That is, in the cutting process, the outer peripheries of the plurality of first stacks 10 forming the second stack 100 can be cut or ground at once with the end mill 50. In the cutting process, the corners at both ends of the concave portion 13 and the corners at the four corners of the first stack 10 can each be chamfered.

[0128] The amount of cutting by the end mill in the cutting step may be, for example, 10 μm or more and 500 μm or less, and preferably 50 μm or more and 150 μm or less.

[0129] The cutting process may be repeated three or more times. For example, in the third cutting process, the first stack 10 is not substantially cut, but the chips generated in the second cutting process are removed from the end surface of the first stack 10. In each cutting process, a plurality of end mills may be used.

[0130] The feed rate of the end mill in the cutting process can be 100 mm / min or more and less than 3000 mm / min. The rotation speed of the end mill in the cutting process can be, for example, 500 rpm or more and 60000 rpm or less, preferably 10000 rpm or more and 60000 rpm or less. The cutting angle in the cutting process can be, for example, 30° or more and 70° or less, preferably 45° or more and 65° or less. When the helix angle of the end mill 50 is α, the cutting angle β is defined as 90°-α. Fig.11 As shown, the helix angle α of the end mill 50 is the angle formed by the direction d1 in which the blade 50e extends on the side of the end mill 50 and the rotation axis 50a of the end mill 50. The cutting angle β can also be changed to the angle formed by the direction d1 in which the blade 50e extends and the direction d2 perpendicular to the rotation axis 50a. The diameter φ (thickness) of the end mill 50 used in the cutting process can be, for example, 3.0 mm or more and 6.0 mm or less.

[0131] (Alkali treatment process)

[0132] The alkali treatment can be performed by contacting an alkaline solution with the end of the resin film containing boric acid and iodine contained in the first laminate. By subjecting the end of the resin film containing boric acid and iodine to alkali treatment, a low boric acid concentration portion and a low iodine concentration portion can be formed. The alkali treatment can be performed on the second laminate overlapped with, for example, 5 or more and 3000 or less of the first laminate. The number of sheets overlapping the first laminate is preferably 7 or more, for example, 2000 sheets, or 1000 sheets.

[0133] The alkaline solution used in the alkaline treatment preferably contains water. The alkaline solution can be, for example, a solution in which a strong alkaline compound is dissolved in a solvent, preferably an aqueous solution of a strong alkaline compound. The strong alkaline compound preferably includes sodium hydroxide and / or potassium hydroxide.

[0134] The temperature of the alkaline solution in contact with the end of the resin film containing boric acid and iodine can be a temperature below 50°C. From the viewpoint of suppressing the reduction in optical properties (reduction in polarization degree, change in color tone, etc.) caused by the orientation disorder of the polarizer in the polarizing plate and reducing the boric acid concentration, the temperature is preferably below 45°C, more preferably below 40°C, and usually above room temperature.

[0135] The time for contacting the end of the resin film containing boric acid and iodine with the alkaline solution can be within 6 minutes. From the viewpoint of suppressing the reduction in optical properties (reduction in polarization degree, change in hue, etc.) caused by the orientation disorder of the polarizer in the polarizing plate and reducing the boric acid concentration, the time can preferably be within 5 minutes, and is usually greater than 1 minute.

[0136] The concentration of the alkaline compound in the alkaline solution may be, for example, 0.1 mol / L to 4 mol / L, preferably 1 mol / L to 3 mol / L, and more preferably 1.5 mol / L to 2.5 mol / L.

[0137] Examples of methods for bringing the end of a resin film containing boric acid and iodine into contact with an alkaline solution include a method of immersing the entire or a portion of the first stack or the second stack in a tank containing an alkaline solution, and a method of spraying the alkaline solution onto the entire or a portion of the first stack or the second stack.

[0138] After contacting the alkaline solution, the resin film containing boric acid and iodine may be washed with water. The washing is preferably performed twice or more. The washing may be performed, for example, by immersing the first laminate or the second laminate in a tank containing water and / or spraying water on the first laminate or the second laminate.

[0139] The polarizing plate of this embodiment can be obtained by the above method.

[0140] <Image display device>

[0141] The above-mentioned polarizing plate can be used for an image display device. As the image display device, for example, a liquid crystal display device, an organic EL display device, etc. can be cited. The polarizing plate can be used for a polarizing plate configured on the visible side of the image display device, and can also be used for a polarizing plate configured on the backlight side of the image display device, and can also be used for polarizing plates on both sides of the visible side and the backlight side. Since it is not easy to make the bleached part conspicuous, the polarizing plate of this embodiment is not easy to damage the design even when used on the visible side of the image display device. Therefore, the image display device is suitable for use as an image display device with a camera hole, for example, as an image display device used in mobile devices such as smart phones and mobile phones and personal computers.

[0142] Example

[0143] The present invention will be described in further detail below using Examples. "%" and "parts" in the examples are by mass % and by mass parts unless otherwise specified.

[0144] [Condensation thermal shock test]

[0145] In each of the examples and comparative examples, three polarizing plates were tested according to the following procedures.

[0146] (1) The optical film side surface of the polarizing plate having a thickness of 21 μm was bonded to the surface of a glass plate (manufactured by Corning) wiped with ethanol via an adhesive layer and subjected to autoclave treatment (50° C., 0.5 MPa, 20 minutes).

[0147] (2) After the autoclave treatment, two locations in the end regions of the corners of the concave portions of the polarizing plate ( Fig.15 It was confirmed that there were no cracks in the area surrounded by circles.

[0148] (3) The polarizing plate was placed in a condensation heat shock oven, and the following operation was repeated 10 times as one cycle.

[0149] First, the polarizing plate was kept at -40°C for 30 minutes and cooled. Then, it was exposed to the outside air at 25°C for 5 minutes. Thereafter, it was heated to 85°C and kept at 85°C for 30 minutes. Thereafter, it was cooled to 25°C, kept for 5 minutes, and then cooled to -40°C. It should be noted that when exposed to the outside air at 25°C for 5 minutes, condensation formed on the surface of the polarizing plate, and then, it was heated to 85°C while maintaining the condensation state. The condensation state of the polarizing plate after being kept at 85°C was eliminated.

[0150] (4) The polarizing plate was taken out from the condensation heat shock oven, and the number, average length, and maximum length of cracks generated at the two corners of the concave portion observed with an optical microscope in (2) were measured using an optical microscope. In addition, the distance from the end of the polarizing plate to the region where the low iodine concentration portion was formed was measured using an optical microscope.

[0151] [Determination of Boric Acid Concentration]

[0152] The borate ion (BO3 3- ) concentration distribution. Fig.13 As shown, the protective film on the side of the optical film 5 (thickness 52 μm) attached to the polarizing plate 110 is peeled off, and the separator on the adhesive layer attached to the side of the optical film 9 (thickness 21 μm) is peeled off, and one part of the end region of the corner including the concave portion is cut out with a width of 100 μm and a length of 1 mm (1000 μm) toward the inside of the polarizing plate to prepare the measurement sample 200. The measurement sample 200 sequentially comprises an optical film 201 (thickness 52 μm), an adhesive layer 202 (thickness 1 μm), a polarizer 203 (thickness 8 μm), an adhesive layer 204 (thickness 1 μm), an optical film 205 (thickness 21 μm), and an adhesive layer 206 (thickness 20 μm). The measurement area 207 in the side of the length direction (1000 μm) of the measurement sample 200 is scanned while irradiating the ion beam to obtain a two-dimensional distribution of the signal intensity of the borate ions in the side, and a portion corresponding to the side of the polarizer is cut out according to the obtained two-dimensional distribution, and the cumulative value of the signal intensity is plotted relative to the length direction of the measurement sample 200 to obtain the distribution of the boric acid concentration relative to the length direction. The conditions of time-of-flight secondary ion mass spectrometry (TOF-SIMS) are shown below.

[0153] In addition, although the boric acid concentration is measured in the state of a polarizing plate, the obtained boric acid concentration can be regarded as the boric acid concentration of the polarizer.

[0154] Device name: Product name: PHI TRIFT V nano TOF (Ulvac-Phi Co., Ltd.)

[0155] Irradiated primary ions: Au3 +

[0156] Primary ion acceleration voltage: 30kV

[0157] Spatial resolution of ion beam: 1μm×1μm

[0158] Measurement area: 200 μm × 200 μm

[0159] Based on the obtained boric acid concentration distribution, the average value of the boric acid ion strength in the range of 30 μm to 60 μm from the end is calculated, and the position from the end to where the boric acid ion strength is the above average value is defined as a low boric acid concentration portion, and the length of the region where the low boric acid concentration portion is formed from the end of the polarizing plate (the length of the low boric acid concentration portion) is measured.

[0160] [Evaluation of low iodine concentration areas]

[0161] The alkali-treated portion of the polarizing plate was observed with an optical microscope using transmitted light. The optical microscope image was imported into a personal computer, and the length of the region where the low iodine concentration portion was formed from the edge of the polarizing plate (the length of the low iodine concentration portion) was measured as follows.

[0162] In the optical microscope image imported into the personal computer, the low iodine concentration part looks bright and the inner area looks dark. The optical microscope image is subjected to image processing, and the brightness of the low iodine concentration part is 180-220, and the brightness of the inner area is 100-140, and it is converted into a 256-level black and white image (brightness 255 is white, 0 is black), and the area with a brightness of more than 180 (white) is regarded as the low iodine concentration part, and the average value of its length from the end is calculated.

[0163] [Production of polarizing plate]

[0164] (First Laminated Body)

[0165] In reference Fig.14At the same time, the preparation of the first laminate 10 is described. A pair of optical films 5 and 9 are attached to a polarizer 7 via adhesive layers 6 and 8, thereby forming the first laminate 10. The first laminate 10 is rectangular. In the first laminate 10, the polarizer 7 is arranged between the pair of optical films 5 and 9. The pair of optical films 5 and 9 are both formed of cyclic olefin polymer resin. The polarizer 7 is a film-shaped polyvinyl alcohol that has been stretched and dyed.

[0166] An adhesive is applied to the optical film 9 side of the first laminate 10 to form an adhesive layer 41, and a separator 42 is bonded thereon. The separator 42 can be peeled off from the adhesive layer. A protective film 43 is bonded to the optical film 5 side of the first laminate 10.

[0167] The protective film 43 can be peeled off from the optical film 5 .

[0168] The thickness of the optical film 5 attached to one surface of the polarizer is 52 μm. The thickness of the optical film 9 attached to the other surface of the polarizer is 21 μm. The thickness of the polarizer 7 is 8 μm. The thickness of the first laminate 10 as a whole is 103 μm. The adhesive layer 6 sandwiched between the optical film 5 with a thickness of 52 μm and the polarizer 7 is a polyvinyl alcohol resin (water paste). The adhesive layer 8 sandwiched between the optical film 9 with a thickness of 21 μm and the polarizer 7 is a UV curable epoxy resin.

[0169] (Special Shape Processing)

[0170] According to the above steps, 47 first laminates 10 are prepared, each of which has an adhesive layer 41 formed on the optical film 9 side, a separator 42 bonded thereto, and a protective film 43 bonded on the optical film 5 side. A concave portion is formed on the short side of each first laminate by punching using a Thomson knife. The shape of the concave portion is the same in all 47 first laminates. A second laminate is produced by stacking the 47 first laminates with the concave portions formed thereon. In the second laminate, the long sides and short sides of all 47 first laminates are aligned, and the concave portions are also aligned.

[0171] After the punching process, the following three cutting steps are performed. In any cutting step, the second stack is fixed with a clamp, and the rotating end mill is moved along the outer periphery (including the outer periphery of the recessed portion) of the second stack while the side of the end mill contacts the outer periphery (end face) of the second stack. That is, the entire outer periphery of each of the 47 sheets of the first stack is cut together with the end mill. The end mill used in each cutting step is DXL-4 manufactured by Nissin Tool Co., Ltd. The cutting angle β is the value shown in Table 1 below. The diameter φ of the end mill is 4 mm.

[0172] The amount of cutting in the first cutting step was the value shown in the following Table 1. The rotation speed (R) of the end mill in the first cutting step was 30000 rpm. The feed speed (V) of the end mill in the first cutting step was 1000 mm / min.

[0173] The amount of cutting in the second cutting step was the value shown in the following Table 1. The rotation speed (R) of the end mill in the second cutting step was 30000 rpm. The feed speed (V) of the end mill in the second cutting step was 1000 mm / min.

[0174] The amount of cutting in the third cutting step was the value shown in the following Table 1. The rotation speed (R) of the end mill in the third cutting step was 30000 rpm. The feed speed (V) of the end mill in the third cutting step was 1000 mm / min.

[0175] By the above method, 47 polarizing plates were produced. The shape, size and stacking structure of each polarizing plate were the same. The overall shape of each polarizing plate was a rectangle. Fig.15 The shape of the obtained polarizing plate 110 when viewed from above is shown in FIG. Fig.15 As shown, the polarizing plate 110 has a quadrangular concave portion 113 formed on a short side. The length of the short side of the polarizing plate 110 is 70 mm.

[0176] The length of the long side of the polarizing plate 110 is 140 mm. The width 111 of the concave portion 113 is 30 mm. The depth 112 of the concave portion 113 is 5 mm. In addition, the depth direction of the concave portion 113 is parallel to the absorption axis (stretching direction).

[0177] <Example 1>

[0178] Ten polarizing plates processed into the above-described shape were stacked, and the end portions were subjected to an alkali treatment under the following conditions and procedures, thereby obtaining a polarizing plate of Example 1.

[0179] (1) Immerse in a 2 mol / L, 40°C NaOH aqueous solution for 5 minutes.

[0180] (2) The laminated polarizing plates were then washed in water washing tank 1 (20° C.) and water washing tank 2 (20° C.) for 1 minute each.

[0181] After the above-mentioned end alkali treatment, the three polarizing plates were subjected to the measurement of boric acid concentration and the condensation heat shock test. The results are shown in Table 1. Fig.16 The TOF-SIMS analysis result (a) and the optical microscope observation image of the end region (b) are shown.

[0182] The polarizing plate has a low boric acid concentration portion formed in a region including the end portion with a width of 20 μm from the end portion. The polarizing plate also has a low iodine concentration portion formed in a region including the end portion with a width of 50 μm from the end portion.

[0183] <Comparative Example 1>

[0184] The three polarizing plates processed into the above-mentioned shapes were subjected to the measurement of boric acid concentration and the condensation heat shock test without the end alkali treatment of Example 1. The results are shown in Table 1. Fig.17 The TOF-SIMS analysis result (a) and the optical microscope observation image of the end region (b) are shown.

[0185] The polarizing plate had a low boric acid concentration portion formed in a region including the end portion with a width of 12 μm from the end portion. In addition, the polarizing plate had no low iodine concentration portion formed in a region including the end portion.

[0186] <Comparative Example 2>

[0187] A polarizing plate of Comparative Example 2 was obtained in the same manner as in Example 1, except that the polarizing plate was immersed in the NaOH aqueous solution for 1 minute instead of 5 minutes. Fig.18 The TOF-SIMS analysis result (a) and the optical microscope observation image of the end region (b) are shown.

[0188] The polarizing plate has a low boric acid concentration portion with a width of 14 μm from the end in a region including the end, and a low iodine concentration portion with a width of 18 μm from the end in a region including the end.

[0189] [Table 1]

[0190] Example 1 Comparative Example 1 Comparative Example 2 Number of cracks 316 349 312 Average crack length (μm) 573 856 708 Maximum crack length (μm) 1210 1760 1810 Length of low boric acid concentration area (μm) 20 12 14 Length of low iodine concentration area (μm) 50 0 18

[0191] In Example 1, the number of cracks is small, the average crack length and the maximum crack length are short, and the area where the low iodine concentration portion is formed is very small.

[0192] In Comparative Example 1, the number of cracks was large, the average crack length and the maximum crack length were long, and the occurrence of cracks was not suppressed.

[0193] In Comparative Example 2, although the number of cracks was reduced, the average crack length and the maximum crack length were long, and cracks were not sufficiently suppressed.

[0194] According to the present invention, it is possible to obtain a polarizing plate in which the generation of cracks is suppressed in the above-mentioned condensation heat shock test and deiodination is not noticeable.

[0195] Description of Reference Numerals

[0196] 1 polarizing plate, 2 polarizing plate, 3 first optical film, 4 second optical film, 5, 9 optical film, 7 non-alkali treated polarizing plate, 10 first laminate, 11 region I, 12 region II, 13, 113 concave portion, 14 through hole, 15 third optical film, 20 image display device, 21 polarizing plate, 22 camera hole, 23 liquid crystal panel, 24 cover glass, 25 adhesive layer, 26 polarizing plate, 27 camera, 28 light shielding tape, 30 low boric acid concentration portion, 31 intermediate region domain, 32 inner region, 33 low iodine concentration area, 34 middle region, 41 adhesive layer, 42 isolation film, 43 protective film, 50 end mill, 50a rotation axis, 50e blade (edge), 100 second stack, 110 polarizing plate, 111 width, 112 depth, 200 measurement sample, 201, 205 optical film, 202, 204 adhesive layer, 203 polarizer, 206 adhesive layer, 207 measurement area, α helix angle, β cutting angle.

Claims

1. A polarizing plate comprising: a polarizing plate which is a resin film containing boric acid and iodine, and optical films arranged on both sides of the polarizing plate, At least one of the optical films comprises a cyclic olefin polymer resin, The polarizing plate forms a low boric acid concentration portion in a region including the end portion when viewed from above, wherein the concentration of boric acid in the low boric acid concentration portion is lower than the concentration of boric acid in an inner region at an inner distance of 500 μm or more relative to the end portion. The low boric acid concentration portion is formed in a region that is 15 μm or more and less than 50 μm inward from the end portion in a plan view. The polarizing plate forms a low iodine concentration portion in a region including the end portion, wherein the iodine concentration in the low iodine concentration portion is lower than the iodine concentration in the inner region, In the polarizing plate, the length of the low iodine concentration portion from an end portion is 19 μm to 100 μm.

2. The polarizing plate according to claim 1, wherein The concentration of boric acid in the low boric acid concentration portion decreases as it approaches the end portion from the inner side in a plan view of the polarizing plate.

3. The polarizing plate according to claim 1, wherein The low boric acid concentration portion and the low iodine concentration portion are formed along an outer edge portion of the polarizer.

4. The polarizing plate according to any one of claims 1 to 3, wherein The polarizing plate has a irregular shape portion in a plan view, and the low boric acid concentration portion and the low iodine concentration portion are formed in an end region included in the irregular shape portion.

5. The polarizing plate according to claim 4, wherein The irregularly shaped portion is a concave portion provided at the peripheral portion, or a through hole provided in the polarizing plate surface. 6 . An image display device comprising the polarizing plate according to claim 1 . The image display device according to claim 6 , having a camera hole.

8. A method for producing a polarizing plate according to claim 1, wherein the polarizing plate comprises a polarizer which is a resin film containing boric acid and iodine, and an optical film disposed on one side or both sides of the polarizer, The manufacturing method includes an alkali treatment step of bringing an alkaline solution at a temperature of 45° C. or less into contact with an end portion of the resin film containing boric acid and iodine for a period of more than 1 minute and within 6 minutes.

9. The method for manufacturing a polarizing plate according to claim 8, wherein: The alkaline solution comprises water.

10. The method for manufacturing a polarizing plate according to claim 8, wherein: The alkaline solution is a solution in which a strong alkaline compound is dissolved in a solvent.

11. The method for manufacturing a polarizing plate according to claim 10, wherein: The strong alkaline compound comprises sodium hydroxide and / or potassium hydroxide.

12. The method for producing a polarizing plate according to any one of claims 8 to 11, further comprising a forming step of forming the resin film containing boric acid and iodine into a predetermined shape by cutting and / or punching, The resin film subjected to the forming step is subjected to the alkali treatment step.